Bank restructuring, competition, and lending supply: Evidence from the Spanish banking sector - Pierpaolo Giannoccolo; José Manuel Mansilla-Fernández (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
This article analyses the effects of the bank restructuring process performed in Spain between 2010 and 2016. First, we create a unique dataset by combining information from Bankscope and the Table of Public Financial Assistance released by the Bank of Spain. Second, we investigate whether these reforms affected (i) the stability, (ii) the degree of competition, and (iii) lending and liquidity supply of the Spanish banking industry. The main results suggest that the restructuring process reduced the degree of competition but increased financial stability in the Spanish banking industry. In particular, we find that two divergent forces affected the Spanish financial stability. On the one hand, the bail out dampened financial instability. On the other hand, the increasing bank market power fostered financial stability (i.e., lower risk-taking behaviour). Furthermore, we demonstrate that the restructuring process: (i) increased the Lerner index, (ii) did not increase the collusion among banks (iii) diminished the gap in cost efficiency between weak and healthy banks. Finally, we find that there are not improvements in lending and liquidity supply.
Keywords: G21; G28; G32; G34; 330; Bank bail-out; bank restructuring process; financial stability; lending availability; liquidity creation; Boone indicator